Hypoxia-induced sensitisation of TRPA1 in painful dysesthesia evoked by transient hindlimb ischemia/reperfusion in mice - So, Kanako (Sci Rep, 2016)
Dysesthesia is an unpleasant abnormal sensation, which is often accompanied by peripheral neuropathy or vascular impairment. Here, we examined the roles of transient receptor potential ankyrin 1 (TRPA1) in dysesthesia-like behaviours elicited by transient hindlimb ischemia (15–60 min) by tightly compressing the hindlimb, and reperfusion by releasing the ligature. The paw-withdrawal responses to tactile stimulation were reduced during ischemia and lasted for a while after reperfusion. Hindlimb ischemia/reperfusion elicited spontaneous licking of the ischemic hindpaw that peaked within 10 min. The licking was inhibited by reactive oxygen species (ROS) scavengers, a TRPA1 antagonist, or TRPA1 deficiency, but not by TRPV1 deficiency. In human TRPA1-expressing cells as well as cultured mouse dorsal root ganglion neurons, the H(2)O(2)-evoked TRPA1 response was significantly increased by pretreatment with hypoxia (80 mmHg) for 30 min. This hypoxia-induced TRPA1 sensitisation to H(2)O(2) was inhibited by overexpressing a catalytically-inactive mutant of prolyl hydroxylase (PHD) 2 or in a TRPA1 proline mutant resistant to PHDs. Consistent with these results, a PHD inhibitor increased H(2)O(2)-evoked nocifensive behaviours through TRPA1 activation. Our results suggest that transient hindlimb ischemia/reperfusion-evoked spontaneous licking, i.e. painful dysesthesia, is caused by ROS-evoked activation of TRPA1 sensitised by hypoxia through inhibiting PHD-mediated hydroxylation of a proline residue in TRPA1.